Close Relatives, Different Niches: Urban Ecology of Two Range-Expanding Thrushes Recently Meeting in the Argentinian Pampas - Vazquez, Miriam Soledad (2025)
Urbanization reshapes bird communities by filtering species according to their ecologicaltraits, often reducing richness, altering relative abundances, and favoring a subset offunctionally tolerant species that dominate urban assemblages. Some native taxa are ableto inhabit cities, even using them as stepping stones for range expansion. We examinedurban habitat use, microhabitat selection, and potential niche partitioning between tworange-expanding thrushes (Austral Thrush [Turdus falcklandii] and Rufous-bellied Thrush[Turdus rufiventris]) in two urban settlements in the Pampas region, Argentina. Using131 transects across green areas and urbanized zones, we related abundance patterns tohabitat features at the transect scale and evaluated microhabitat selection at the individuallevel. Austral Thrush abundance increased with herbaceous cover, tree cover, and evenconcrete surfaces, suggesting a relatively high tolerance to fragmented green spaces withindense urban matrices. In contrast, Rufous-bellied Thrush showed a positive associationwith tree cover, avoided tall buildings, and reached higher abundance in the smaller city,consistent with its recent arrival in the region and preference for less intensively urbanizedenvironments. Microhabitat data revealed marked vertical stratification: Austral Thrushforaged almost exclusively at ground level on grassy or bare substrates, while RufousbelliedThrush used trees, shrubs, and vines more frequently. These differences reflectfine-scale resource partitioning that may contribute to reducing niche overlap and favorthe coexistence of both species in recently colonized urban areas, while recognizing thatsuch dynamics occur within broader bird assemblages where multiple species interact andcompete for space and resources. Our findings highlight that even closely related species can respond divergently to urban structure, and that maintaining structural and substrateheterogeneity within cities may help support native bird diversity.